Pelatihan Pembuatan “Samijel” (Sabun Berbasis Minyak Jelantah Dan Eco Enzyme) Untuk Menjaga Kesehatan Lingkungan Pada Kader Pemberdayaan Kesejahteraan Keluarga (Pkk) Desa Candirejo, Kabupaten Semarang - Yuswantina, Richa; Dyahariesti, Niken; Lestari, Ita Puji (Jurnal Pengabdian Masyarakat (ABDIRA), 2024)
Used cooking oil comes from cooking oil that has been used many times so that it can change its physical and chemical structure. In Indonesia, many people use cooking oil repeatedly because it is a shame to throw it away and there is a lack of understanding about the dangers of used cooking oil. The purpose of this activity is to increase the level of knowledge and increase the skills of PKK Cadres of Candirejo Village, Semarang Regency regarding the handling of used cooking oil as household waste and the manufacture of reusable products from used cooking oil waste to improve environmental health. The solution offered in this community service activity is to provide counseling, education and training to PKK Cadres of Candirejo Village who become an educational bridge for partners and community service resource persons. The approach is carried out using the methods of observation, interviews, counseling, demonstration of how to make "Samijel" soap. From the results of the community service training activities, it was found that there was a difference in the level of knowledge of PKK Cadres of Candirejo Village between before and after the training activities were given.